Anti-Mycobacterium tuberculosis activity of platinum(II)/N,N-disubstituted-N′-acyl thiourea complexes - Plutín, Ana M.; Alvarez, Anislay; Mocelo, Raúl; Ramos, Raúl; Castellano, Eduardo E.; Da Silva, Monize M.; Colina-Vegas, Legna; Pavan, Fernando R. [UNESP]; Batista, Alzir A. (Elsevier, 2016)
Synthesis, characterization and anti-Mycobacterium tuberculosis assays of new platinum(II)/dppf/N,N-disubstituted-N′-acyl thiourea complexes with general formulae [Pt(dppf)(L)]PF6, [dppf = 1,1′-bis(diphenylphosphino)ferrocene; L = N,N-disubstituted-N′-acyl thioureas] is reported. The complexes were characterized by elemental analysis, molar conductivity, IR, NMR (1H, 13C and 31P{1H}) spectroscopy. The spectroscopic data are consistent with the complexes containing one dppf and one O, S chelated ligand. The crystal structures of complexes with N,N-diphenyl-N′-benzoylthiourea (L4), N,N-diethyl-N′-furoylthiourea (L5) and N,N-diphenyl-N′-(thiophene-2-carbonyl)thiourea (L8) were determined by X-ray crystallography, confirming the coordination of the ligands with the metal through sulfur and oxygen atoms, forming distorted square-planar structures. The complexes were screened with respect to their anti-M. tuberculosis activity (H37Rv ATCC 27294).
Keywords: 1 1′-Bis(diphenylphosphino)ferrocene; Anti-Mycobacterium tuberculosis assays; N N-Disubstituted-N′-acyl thioureas; Platinum(II) complexes